ANALYSIS OF DIVISION OF LABOR AND EMPLOYEE AUTHORITY IN IMPROVING WORK PERFORMANCE - Sultoni, Riza Faqih (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to determine the overview of work division, employee authority, and job performance at PT. Anala Cakra Energi, as well as to analyze the influence of work division and authority on employee performance improvement. The research employs descriptive and associative methods with a quantitative approach. The population of this study consists of all employees at PT. Anala Cakra Energi, totaling 33 individuals. Data were collected through questionnaires and analyzed using statistical tests, specifically the t-test. The results of the study indicate that there is no significant influence of work division on employee performance improvement. Similarly, employee authority does not show a significant effect on job performance. This is evidenced by the hypothesis testing, where the t-count values were lower than the t-table values, thus accepting the null hypothesis (H₀) for both variables. Therefore, the current implementation of work division and authority has not provided a significant contribution to improving employee performance at the company.